1989
DOI: 10.2307/3809174
|View full text |Cite
|
Sign up to set email alerts
|

Deer and Cattle Diets on Heavily Grazed Pine-Bluestem Range

Abstract: We studied dietary overlap between captive white-tailed deer (n = 3) (Odocotleus tir@nlanus) and cattle (n = 4) for 3 years on 2 rotationally burned, 54-ha longleaf pine (Pinus paZustris)-bluestem (Andropogon spp.) pastures in central Louisiana. A third of each pasture was burned each year in late February. One pasture was grazed heavily (61-77% herbage use) yearlong; the other was grazed heavily (SO-67% use) from mid-April to 1 November. Deer diets were dominated yearlong by a mixture of browse (49.3~83.2%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…The earlier findings for longleaf pine-bluestem sites (Thill and Martin 1989) revealed substantial dietary overlap between deer and cattle from late fall through early spring, but largely complementary diets the remainder of the year, with deer using mostly browse and forbs and cattle using mostly grasses. From late fall through early spring, deer and cattle both sought diets high in evergreen and tardily deciduous browse and herbaceous winter rosettes.…”
Section: Management Implicationsmentioning
confidence: 87%
See 2 more Smart Citations
“…The earlier findings for longleaf pine-bluestem sites (Thill and Martin 1989) revealed substantial dietary overlap between deer and cattle from late fall through early spring, but largely complementary diets the remainder of the year, with deer using mostly browse and forbs and cattle using mostly grasses. From late fall through early spring, deer and cattle both sought diets high in evergreen and tardily deciduous browse and herbaceous winter rosettes.…”
Section: Management Implicationsmentioning
confidence: 87%
“…Current-year browse production averaged >400 kg/ha on both pastures during phase 1 (Thill and Martin 1989) and was estimated at or slightly above this level during phase 2. Herbage production and use varied with years since last burn (table 1).…”
Section: Study Areas and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Thill and Martin 22 showed that diet overlap between white-tailed deer and cattle on pastures in central Louisiana was greatest in the winter (30.7%). However, the intensity of cattle grazing did not have a major impact on the diet overlap.…”
Section: The Impact Sources Diet Overlapmentioning
confidence: 99%
“…Early summer grazing minimally reduced foraging efficiency of mule deer and elk [25]. Alternatively, Thill and Martin [26] showed that cattle grazing during late fall decreased availability of deer forage, whereas moderate summer grazing did not have this effect. A study of interactions between African cattle and wild ungulates indicated that ungulates competed for food with cattle during the dry season, but improved the cattle's diet quality during the rainy season (Odadi et al 2011).…”
Section: Introductionmentioning
confidence: 99%